Effects of Land Use Change on Soil Aggregate Stability and Erodibility in the Karst Region of Southwest China - Li, Meiting; Wang, Keqin; Ma, Xiaoyi; Fan, Mingsi; Song, Yali (Agronomy (Basel), 2024)
Differences in land use type and chronological age affect soil properties and plant community characteristics, which may influence soil structural stability and erodibility. However, knowledge on the effects of soil physicochemical properties on soil aggregate stability and erodibility at different land use years is limited. This study selected five land use types: corn field (Year 38th-y), corn intercropped with cabbage field (Year 38th-y + b), fruit and meridian forest (Year 6th-jgl), naturally restored vegetation (Year 6th-zr), and artificial forest (Year 7th-rgl) in the karst landscape of the Chishui River Basin in Yunnan Province. We aimed to identify the influencing factors of soil stability and erodibility under different land use time series. The results indicated that the mean weight diameter (MWD), the geometric mean diameter (GMD), and soil structural stability index (SSI values) were highest in Y6th-zr and lowest in Y7th-rgl. Conversely, the erodibility K value was lowest in Y6th-zr, suggesting that the soil structure in Y6th-zr exhibited greater stability, whereas soil stability in Y7th-rgl was lower. Redundancy and throughput analyses revealed that organic carbon and water-stable aggregates > 2.0 mm content had higher vector values. Soil bulk density, total nitrogen, organic carbon, and soil texture content were the main factors contributing to soil stability variation (0.338–0.646). Additionally, total nitrogen, organic carbon, total phosphorus, and soil texture content drove the variation in K values (0.15–1.311). Natural vegetation restoration measures can enhance soil structure to a certain extent. These findings highlight changes in soil aggregate stability and erodibility over different land use durations. The research results have important theoretical and practical significance for understanding the differences in soil erosion and soil restoration under different land use patterns in the karst landscapes of southwest China.